2020
DOI: 10.1002/pbc.28709
|View full text |Cite
|
Sign up to set email alerts
|

Effects of treatments on gonadal function in long‐term survivors of pediatric hematologic malignancies: A cohort study

Abstract: Background: Potentially gonadotoxic protocols are currently used for the treatment of childhood hematologic malignancies. This study aims to evaluate the prevalence of gonadal dysfunction and the most important associated risk factors in a cohort of hematologic malignancy survivors. Procedure: We considered all patients referred to our long-term follow-up clinic for childhood cancer survivors, between November 2001 and December 2017. Inclusion criteria were: (a) previous diagnosis of hematologic malignancy; (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The number of female survivors with POI was reported in seven of the included studies (1516 patients) ( Table II and Supplementary Fig. S1 ) ( Green et al , 1981 ; Sklar et al , 2006 ; Zaletel et al , 2010 ; van der Kaaij et al , 2012b ; Swerdlow et al , 2014 ; Levine et al , 2018 ; Felicetti et al , 2020 ). The percentage of female HL survivors with signs of POI ranged from 6% to 34% (median 9%) and was especially high in patients receiving radiotherapy and BEAM (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of female survivors with POI was reported in seven of the included studies (1516 patients) ( Table II and Supplementary Fig. S1 ) ( Green et al , 1981 ; Sklar et al , 2006 ; Zaletel et al , 2010 ; van der Kaaij et al , 2012b ; Swerdlow et al , 2014 ; Levine et al , 2018 ; Felicetti et al , 2020 ). The percentage of female HL survivors with signs of POI ranged from 6% to 34% (median 9%) and was especially high in patients receiving radiotherapy and BEAM (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Among the eligible studies, the reported percentage of patients with elevated FSH ranged from 0% to 100% (median 51.5%). Nine studies used the generally accepted cutoff value of 10 IU/L to determine high FSH serum level, indicating damage to spermatogenesis ( Sherins et al , 1978 ; Hassel et al , 1991 ; Heikens et al , 1996 ; Mackie et al , 1996 ; Müller et al ., 1996 ; van den Berg et al , 2004 ; Servitzoglou et al ., 2015 ; Brignardello et al , 2016 ; Felicetti et al , 2020 ). The other studies used higher cutoff values (i.e.…”
Section: Resultsmentioning
confidence: 99%
“… 2 In long-term female survivors of pediatric hema tologic malignancies 26.7% experienced premature ovarian insufficiency and face infertility after cancer treatment. 3 The situation is similar with other cancers; cancer therapy is the cause of premature ovarian failure in 25% of women with this diagnosis. 4 Therefore, it is very important to consider the preservation of female fertility before oncotherapy.…”
Section: Introductionmentioning
confidence: 86%
“…Infertility is another well-recognized side effect of HSCT [ 69 , 70 , 71 , 72 ], since the seminiferous tubules in males and the ovaries in females are highly sensitive to the detrimental effects of alkylating agents and RT [ 73 , 74 , 75 ]. Patients exposed to TBI show a significant risk of cataracts [ 76 ] and of skeletal alteration [ 77 ], involving also dental and/or craniofacial skeletal structures, with a clear relation to the age at treatment [ 78 ].…”
Section: Tbi-associated Late Toxicitiesmentioning
confidence: 99%